Intercontinental Multidisciplinary Oncology Videoconferencing for Rare and Complex Cancer: An Alternative to Systematic Transfer. Issue 9 (September 2021) - Honoré, Charles; Mir, Olivier; Geraud, Arthur; Drovetti, Gianmaria; Garcia, Gabriel C. T. E.; Gustin, Pierre; Colomba, Emeline; Pilorge, Sylvain; Matias, Margarida; Majer, Michael; Balleyguier, Corinne; Azoulay, Mikael; et al.
Abstract : PURPOSE: To report our experience of intercontinental multidisciplinary oncology videoconferencing between the French mainland and South Pacific to discuss rare and/or complex cancer cases. METHODS: On the first and third Friday of each month, all participants connected between 6:30 AM and 8:00 AM GMT to discuss using a web conference service. RESULTS: Between November 2019 and April 2020, 99 cases concerning 78 patients were discussed. Oncology subspecialties required were sarcoma (n = 36), digestive (n = 29), dermatology (n = 5), gynecology (n = 5), breast (n = 5), urology (n = 5), hematology (n = 5), ENT (n = 3), thoracic (n = 3), thyroid (n = 2), and pediatric (n = 1). Median patient age was 58 years, 41 were female (53%), 37 were male (47%), and 43 had a metastatic disease (55%). Following discussion, 16 patients (21%) were transferred to the French mainland. Reasons for transfer were requirement for complex surgery (n = 11) and need for specialized diagnostic biopsy (n = 5). Fifty-six patients were treated locally, with systemic chemotherapy (n = 36), surveillance (n = 8), surgery (n = 8), radiotherapy (n = 3), or endoscopy (n = 1). Direct benefits for patients treated in their local facility included strategy changes (surveillance or surgery contraindication, n = 9), targeted therapy decision (n = 14), immunotherapy decision (n = 9), and diagnostic or metastatic status corrections (n = 4). Six patients are still awaiting decision. CONCLUSION: Using real-time intercontinental multidisciplinary oncology videoconferencing to discuss complex or rare cancer cases is reliable and effective for decision making. This concept helped to limit to 21% the need for transfers to the mainland.